Sosialisasi Pemahaman Perbaikan Kualitas Daya Di Industri Bengkel - Putri, Maharani; Ramadhan, Andri (Cattleya Darmaya Fortuna, 2025)
Power quality issues are a critical concern in industrial environments, including automotive workshops and light manufacturing sectors. Disturbances such as voltage sags, harmonics, and low power factor can directly impact machine performance, energy efficiency, and the lifespan of electrical equipment. This outreach program aims to enhance the understanding of workshop operators and technicians regarding the importance of power quality improvement and to introduce practical, cost-effective solutions. The activity was conducted through interactive presentations, group discussions, and demonstrations of power quality improvement tools such as capacitor banks, automatic voltage regulators (AVR), and harmonic filters. Participants included workshop owners, technicians, and electrical maintenance staff from small and medium industries. Evaluation was carried out using pre-tests and post-tests to measure the improvement in participants' comprehension of the topics delivered. The results show a significant increase in participants’ understanding, with post-test scores improving by an average of 35% compared to pre-test scores. Participants also expressed strong interest in applying energy efficiency solutions and maintaining electrical systems. This activity is expected to encourage workshop operators to implement basic power quality management practices, leading to better energy efficiency, improved operational safety, and longer equipment lifespan. Keywords: power quality, automotive workshop, energy efficiency, harmonics, technical outreach